2019
DOI: 10.1111/echo.14263
|View full text |Cite
|
Sign up to set email alerts
|

Early mitral inflow velocity to left ventricular global strain ratio predicts limited exercise capacity

Abstract: Background Estimation of left ventricular filling pressure (LVFP) is the essential part of the echocardiographic workup for exercise intolerance. The ratio of the mitral early filling velocity to the left ventricular global longitudinal strain (E/LVGLS) has emerged as a novel index of LVFP. This study aimed to investigate the relationship between E/LVGLS and exercise capacity. Methods and results We retrospectively reviewed 90 patients with exertional dyspnea who underwent echocardiography and cardiopulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Echocardiography is a reliable method for visual assessment of segmental and global cardiac function 19 . Using Doppler tissue imaging (TDI) to measure the ratio of the early diastolic blood flow peak (E) and the early diastolic movement speed (e′) of the mitral valve cusp at the level of the mitral valve cusp, it can be simple, effective and noninvasive to evaluate the left ventricular filling pressure of the heart and diastolic function 20 , 21 . This study showed that the higher the MIRI manifestation grade is, the larger the LVEDD and E/e′ and the smaller the E/A.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is a reliable method for visual assessment of segmental and global cardiac function 19 . Using Doppler tissue imaging (TDI) to measure the ratio of the early diastolic blood flow peak (E) and the early diastolic movement speed (e′) of the mitral valve cusp at the level of the mitral valve cusp, it can be simple, effective and noninvasive to evaluate the left ventricular filling pressure of the heart and diastolic function 20 , 21 . This study showed that the higher the MIRI manifestation grade is, the larger the LVEDD and E/e′ and the smaller the E/A.…”
Section: Discussionmentioning
confidence: 99%